Healthcare provider perspectives on emergency department-initiated buprenorphine/naloxone: a qualitative study - Katherin Badke; Serena S. Small; Megan Pratt; Julie Lockington; Lara Gurney; Andrew Kestler; Jessica Moe (BMC, 2024)
Abstract Background Take-home buprenorphine/naloxone is an effective method of initiating opioid agonist therapy in the Emergency Department (ED) that requires ED healthcare worker buy-in for large-scale implementation. We aimed to investigate healthcare workers perceptions of ED take-home buprenorphine/naloxone, as well as barriers and facilitators from an ED healthcare worker perspective. Methods In the context of a take-home buprenorphine/naloxone feasibility study at a tertiary care teaching hospital we conducted a descriptive qualitative study. We conducted one-on-one in person or telephone interviews and focus groups with ED healthcare workers who cared for patients given take-home buprenorphine/naloxone in the feasibility study at Vancouver General Hospital from July 2019 to March 2020. We conducted 37 healthcare worker interviews from December 2019 to July 2020. We audio recorded interviews and focus groups and transcribed them verbatim. We completed interviews until we reached thematic saturation. Data analysis We inductively coded a sample of transcripts to generate a provisional coding structure and to identify emerging themes, which were reviewed by our multidisciplinary team. We then used the final coding structure to analyze the transcripts. We present our findings descriptively. Results Participants identified a number of context-specific facilitators and barriers to take-home buprenorphine/naloxone provision in the ED. Participants highlighted ED conditions having either facilitative or prohibitive effects: provision of buprenorphine/naloxone was feasible when ED volume was low and space was available but became less so as ED volume increased and space decreased. Similarly, participants noted that patient-related factors could have a facilitative or prohibitive effect, such as willingness to wait (willing to stay in the ED for study-related activities and buprenorphine/naloxone initiation activities), receptiveness to buprenorphine/naloxone, and comprehension of the instructions. As for staff-related factors, time was identified as a consistent barrier. Time included time available and time required to initiate buprenorphine/naloxone (including time building rapport). Healthcare worker familiarity with buprenorphine/naloxone was noted as either a facilitating factor or a barrier, and healthcare workers indicated that ongoing training would have been advantageous. Many healthcare workers identified that the ED is an important first point of contact for the target patient population. Conclusion Integrating a buprenorphine/naloxone program into ED care requires organizational supports (e.g., for managing buprenorphine/naloxone within limitations of ED volume, space, and time), and ongoing education of healthcare workers to minimize identified barriers.